PENGARUH LATIHAN PLYOMETRIC PADA FUNCTIONAL ANKLE INSTABILITY ATLET TAEKWONDO - Endah Tri Wulandari; Bambang Trisnowiyanto; Fendy Nugroho (Jurnal Nasional Fisioterapi, 2023)
Background: Functional ankle instability is ankle instability that occurs repeatedly and describes an unstable ankle condition, and experiences functional limitations due to decreased proprioceptive processes, decreased neuromuscular function, and decreased postural control ability. To overcome this disorder, the action that can be given to someone who experiences functional ankle instability is in the form of plyometric exercises. Objective: To find out whether there is an effect of plyometric training on functional ankle instability in taekwondo athletes. Method: This research uses one group pretest and posttest design. The subjects of this research were athletes from the Kertajaya Taekwondo community who had met the inclusion and exclusion criteria of 14 athletes with an age range of 9 to 15 years. Subjects were given treatment in 16 meetings over 6 weeks starting from February to March 2023. The measuring tool used in this research was the Cumberland Ankle Instability Tool Youth questionnaire. Results: In this study, to prove that plyometric training has an effect on ankle stability, a hypothesis test was carried out using the Wilcoxon test as part of the non-parametric test, the result was p = 0.01 or p < 0.05, which means there is a significant effect on ankle stability in functional ankle stability of taekwondo athletes. Conclusion: There is an effect of plyometric training on increasing ankle stability in the functional ankle stability of taekwondo athletes